Admission Neutrophil-to-Lymphocyte Ratio as a Prognostic Biomarker of Outcomes in Large Vessel Occlusion Strokes. Issue 8 (August 2018) - Goyal, Nitin; Tsivgoulis, Georgios; Chang, Jason J.; Malhotra, Konark; Pandhi, Abhi; Ishfaq, Muhammad F.; Alsbrook, Diana; Arthur, Adam S.; Elijovich, Lucas; Alexandrov, Andrei V.
Abstract : Background and Purpose—: The purpose of this study is to evaluate the relationship between neutrophil-to-lymphocyte ratio (NLR) at admission with safety and efficacy outcomes in acute stroke patients with large vessel occlusion after mechanical thrombectomy. Methods—: Consecutive large vessel occlusion patients treated with mechanical thrombectomy during a 4-year period were evaluated. Outcome measures included symptomatic intracranial hemorrhage, 3-month mortality, successful reperfusion (modified Thrombolysis in Cerebral Infarction score of 2b/3), and 3-month functional independence (modified Rankin Scale scores of 0–2). Results—: A total of 293 large vessel occlusion patients underwent mechanical thrombectomy (median admission NLR, 3.5; interquartile range [IQR], 1.7–6.8). In initial univariable analyses, higher median admission NLR values were documented in patients with symptomatic intracranial hemorrhage (8.5; IQR, 4.7–11.3) versus (3.9; IQR, 1.9–6.5); P <0.001 and individuals who were dead at 3-months (5.4; IQR, 2.8–9.6) versus (4.0; IQR, 1.8–6.4); P =0.004. Lower NLR values were recorded in patients with 3-month functional independence (3.7; IQR, 1.7–6.5) versus (4.3; IQR, 2.6–8.3); P =0.039. After adjustment for potential confounders, a 1-point increase in NLR was independently associated with higher odds of symptomatic intracranial hemorrhage (odds ratio, 1.11; 95% CI, 1.03–1.20; P =0.006) and 3-month mortality (odds ratio, 1.08; 95% CI, 1.01–1.16; P =0.014). Conclusions—: Higher admission NLR is an independent predictor of symptomatic intracranial hemorrhage and 3-month mortality in large vessel occlusion patients treated with mechanical thrombectomy, and it may identify a target group for testing adjunctive anti-inflammatory therapies. Abstract : Supplemental Digital Content is available in the text.